CONSTRAINTS IN PLANNING AND IMPLEMENTATION OF HIGHER EDUCATION PROGRAMMES IN RIVERS NIGERIA - Onyeike, Victoria C.; Dorothy, Owuama N (European Scientific Journal, ESJ, 2012)
The study aimed at determining the constraints to planning and implementation of higher education programmes was carried out, with emphasis on the six higher institutions in Rivers State. The sample consisted of 450 academic and administrative staff from the rank of Deans, Heads of Departments and Senior Lecturers. The sample was selected by simple random sampling technique from a population of 750 unit heads. A 30-item questionnaire captioned Deans, Heads of Department and Senior Lecturers Assessment Questionnaire (DHDSLAQ) was used to collect data from participants. Mean score and standard deviations were used to answer the research questions, while the Z-test was used to test the hypotheses at P-value of 0.05 or 5% level of significance. The result of the study revealed among others that inadequacy of funds, planning without accurate statistical data, political influence, and misappropriation of funds and shortage of qualified manpower were major constraints. The findings also revealed that there were significant difference between male and female unit heads on the perception of constraints to planning and implementation of higher education programmes. Based on the findings it was recommended among others that both state and federal government should disburse enough money to education sector as to enable educational planners and other professionals in planning to carry out their job effectively.